Amyloid goiter with diffuse thyrolipomatosis: a rare entity - Vallathai, Silpa; Kuruvilla, Shalini; Kanhirangad, Lakshmi; Kanjirakadu Parameswaran, Kavitha; Ahmed Abdulla, Faheem (International Surgery Journal, 2024)
Diffuse thyroid lipomatosis with amyloid deposition is a rare entity. We report a case of a 42-year-old lady who presented with progressive enlargement of the thyroid gland with compressive symptoms. Her thyroid hormone levels were within normal limits. Imaging revealed enlarged thyroid gland with multiple fat density lesions. She underwent total thyroidectomy, and histopathology revealed diffuse infiltration of thyroid stroma by mature adipose tissue and an associated amyloid deposition. A diagnosis of amyloid goiter with diffuse lipomatosis of the thyroid gland was rendered. Only a few cases of diffuse lipomatosis with concurrent deposition of amyloid protein have been reported in the literature.